Efektivitas Peraturan Daerah Kabupaten Wajo No 8 Tahun 2022 Tentang Pengelolaan Sampah - Martono; Ismail Ali; Yustiana; Mustari; Kadek Ade Wahyudi (YP-SDI Lamaddukelleng, 2025)
This study aims to determine the effectiveness of Wajo Regency Regional Regulation Number 8 of 2022 concerning Waste Management. The effectiveness in question is the ability of this regulation to control community behavior in waste management to create a clean and healthy environment. The study is a qualitative study conducted on five informants at the Environmental Service, five informants from cleaning officers and five informants from the community, in order to obtain information the author uses an intervew approach which is then analyzed so that the data produced is easy to understand. The results of the study illustrate that Wajo Regency Regional Regulation Number 8 of 2022 concerning Waste Management is not yet effective, this can be caused by several factors, namely: 1) awareness, 2) supporting facilites, 3) information, 4) law enforcement. Law enforcement must also be firm and fair so that there is legal certainty to create a more effective Wajo Regency Regional Regulation Number 8 of 2022 concerning Waste Management for a cleaner and healther Wajo.